2010
DOI: 10.3109/14767058.2010.511334
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of neonatal myocardial dysfunction

Abstract: CK-MB, mostly of muscle origin and reflecting labor stress or injury, is not to recommend as a measure of myocardial damage in the neonate. The rise in cTnI may be explained by a degree of myocardial involvement, albeit physiological. The initial rise and subsequent fall of NT-proBNP represents the physiological ventricular overload of transient birth adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…The results for CPK-MB activity were recorded as: sensitivity (71.7%), specificity (56.6%), PPV (62.29%), NPV (66.7%), PLR (1.65), and NLR (0.5). They observed a significant elevation in CPK and CPK-MB serum activity in EP and concluded that transvaginal ultrasound (TVS) as better diagnostic tool for EP (64)(65)(66). CORD BLOOD CREATINE KINASE LEVELS Total CK and CK isoenzyme activity in serum during pregnancy, labor and after delivery as well as in cord blood was estimated in a study by Chemnitz and others.…”
Section: Creatine Kinase In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…The results for CPK-MB activity were recorded as: sensitivity (71.7%), specificity (56.6%), PPV (62.29%), NPV (66.7%), PLR (1.65), and NLR (0.5). They observed a significant elevation in CPK and CPK-MB serum activity in EP and concluded that transvaginal ultrasound (TVS) as better diagnostic tool for EP (64)(65)(66). CORD BLOOD CREATINE KINASE LEVELS Total CK and CK isoenzyme activity in serum during pregnancy, labor and after delivery as well as in cord blood was estimated in a study by Chemnitz and others.…”
Section: Creatine Kinase In Pregnancymentioning
confidence: 99%
“…The rise in cTnI may be explained by a degree of myocardial involvement. The initial rise and subsequent fall of NT-proBNP represents the physiological ventricular overload of transient birth adaptation (64). Nakajima and Masaoka determined whether the tocolytic therapy affects CK activity in the umbilical blood.…”
Section: E J M Rmentioning
confidence: 99%
“…Almeida et al (2011) detected low concentrations of cTnI in human cord blood. However, in otherwise normal neonates' maximal increases in cTnI concentrations peaked between 48 and 72 hr after birth and declined by 50% by the 10th day of life (Almeida et al 2011).…”
Section: Cardiac Pathologymentioning
confidence: 99%
“…Almeida et al (2011) detected low concentrations of cTnI in human cord blood. However, in otherwise normal neonates' maximal increases in cTnI concentrations peaked between 48 and 72 hr after birth and declined by 50% by the 10th day of life (Almeida et al 2011). The finding that elevated serum troponin concentrations were more common in normal neonatal blood than in umbilical cord blood is consistent with other studies that found maximal FIGURE 3.-Age comparison of serum cardiac troponin I concentrations in patas monkeys at birth, 2, 6 months, and 1 year of age.…”
Section: Cardiac Pathologymentioning
confidence: 99%
See 1 more Smart Citation